Úloha lidských a živočišných sérových lektinů vázajících manan nebo fosfomanan v obraně proti infekci - Dlabač, Vladimír (Iga MZ ČR, 2001)
Serum lectins will be isolated and their concentrations in sera of healthy and immunodeficient individuals with recurrent infections will be quantitatively estimated. Aminoacid sequences of lectins binding mannan and/or phosphomannan will be compared.
Závěrečná zpráva o řešení grantu Interní grantové agentury MZ ČR
Keywords: mannosidy; Mannosephosphates; mannosafosfáty; Lectins; vazba proteinů; baktericidní aktivita krve; alergologie a imunologie; lektiny; Protein Binding; vztahy mezi strukturou a aktivitou; Mannosides; Structure-Activity Relationship; Blood Bactericidal Activity